Philippine medical thesaurus on anatomy body regions in Iluko - Sirios, Cristina Noelle S. (School of Library and Information Studies, University of the Philippines Diliman, 2003)
This study is a part of the Multilingual Philippine Medical Thesaurus Project, one of the initiatives emanating from the collaborative efforts of the Institute of Library and Information Science, University of the Philippines Diliman and the College of Medicine, University of the Philippines Manila. The partnership started last December 2002 with the signing of the Memorandum of Agreement covering collaborative efforts in medical informatics research. The need for such a unifying thesaurus was the result of the rapid growth of information in the medical field.